Validation of the mindray BC6000 hematology analyzer for erythroblast counting in peripheral blood - Lacy Brito Junior; Adna dos Santos Caldas; Vanessa Ingrid Cardoso Pereira; Roberta Isabella Senna Ferreira; Ana Paula Silveira Paixão (Sociedade Brasileira de Patologia Clínica, 2022)
ABSTRACT Introduction Differential counting of erythroblasts in blood samples by hematology analyzers still has limitations. Technological advances in blood count equipment have proposed the fully automated counting of these cells, however, not without its validation. Objective Validate the automated count of erythroblasts in peripheral blood in the Mindray BC6000 hematology analyzer and verify the existence of correlation of the maturation stages of erythroblasts with the equipment's graphics. Material and Methods Prospective study with peripheral blood samples from the Clinical Pathology Laboratory Dr Paulo C. Azevedo, regardless of age and gender, to validate the erythroblast count in the Mindray BC6000 hematology analyzer compared to the manual method (gold standard), in the period of June 2019 to December 2020. Results Seventeen peripheral blood samples were analyzed from newborns (09/17 - 52.3%) and from patients older than 2 years (08/17 - 47.7%) who had more than 18% of erythroblasts after morphological analysis of the sample. Statistical analysis of erythroblast counts by the two methodologies showed that the Mindray BC6000 hematological counter has good reproducibility, precision and linearity. There was no correlation between the maturation stages of erythroblasts and the equipment graphics. Conclusion The proposed validation showed that the Mindray BC6000 hematological counter has good analytical performance for counting erythroblasts in peripheral blood. However, there is no correlation between the maturation stages of erythroblasts with the graphics generated by the equipment.